Correction Maneuver Optimization to Maintain The Local Time of Lapan-A4 Satellite - Zuhri, Muhammad Rizki; Poetro, Ridanto Eko; Indriyanto, Toto; Faturrohim, Luqman (Indonesian Journal of Aerospace, 2023)
In order for a satellite to achieve a sun-synchronous orbit (SSO), it must have a nodal precession rate equal to the revolution rate of the Earth around the Sun. However, sun-synchronous satellites generally encounter significant perturbations, which lead the local time of the satellite to drift gradually. In this research, the author analyzed potential maneuvers to maintain the local time of an SSO satellite for 5 years of operation of LAPAN-A4 satellite. The analysis was conducted by simulation using GMAT (General Mission & Analysis Tools) software with the LAPAN-A4 satellite as a case study. Furthermore, this research also attempted to find the optimum maneuvering period for each potential maneuver. The results showed that the RAAN correction maneuver is ineffective. It was also found that the most optimum maneuvering plan obtained from this research was a semi-major axis correction maneuver with 4 month maneuvering period with a particular correction targeting strategy.